Sex-specific responses to self-paced, high-intensity interval training with variable recovery periods - Laurent, C. M.; Vervaecke, L. S.; Kutz, M. R.; Green, J. M. (The Journal of Strength and Conditioning Research, 2014)
This study examined sex-specific responses during self-paced, high-intensity interval training (HIIT). Sixteen (8 men and 8 women) individuals completed a peak oxygen uptake test and 3 treadmill HIIT sessions on separate days. The HIIT sessions consisted of six 4-minute intervals performed at the highest self-selected intensity individuals felt they could maintain. Recovery between intervals was counterbalanced and consisted of 1-, 2-, or 4-minute recovery during each trial. Relative measures of intensity, including percentage of velocity at VO2peak (vVO2peak), %VO2peak, %HRmax, and blood lactate concentration ([La]), were observed during the trials. Perceived readiness was recorded immediately before and ratings of perceived exertion (RPE) were recorded at the end of each interval with session RPE recorded after each trial. Results revealed a significant effect of sex on %vVO2peak (p < 0.01) and %HRmax (p < 0.01). Data show that across trials, men self-select higher %vVO2peak (84.5 vs. 80.7%), whereas women produce higher %HRmax (96.9 vs. 92.1%) and %VO2peak (89.6 vs. 86.1%) with no difference in [La] or perceptual responses. These findings support the notion that women may demonstrate improved recovery during high-intensity exercise, as they will self-select intensities resulting in greater cardiovascular strain. Moreover, results confirm previous findings suggesting that a 2:1 work-to-rest ratio is optimal during HIIT for both men and women.